Pengujian Determinan Konservatisma Akuntansi - Lasdi, Lodovicus (Widya Mandala Surabaya Catholic University, 2009)
This paper examines the determinants of accounting conservatism. Accounting conservatism is defined as managerial accounting choices of accounting methods and estimates within Generally Accepted Accounting Principle (GAAP) that result in the persistence understatement of cumulative reported earnings and net assets over period of time. In this paper, I empirically tests the set of factors purported by Watts (2003a) as determinants of conservatism.This set of determinants relates to incentives arising from contracting (debt and compensation), litigation, tax, and political costs. I find evidence consistent with debt contracting and litigation, but not consistent with compensation contracting and tax and political costs.